Surface Texturing and Alternative Lubricant: Tribological Study of Tapered Die Sliding Contact Surface in Cold Extrusion Process. Issue 1 (2nd January 2017) - Nurul, M. A.; Syahrullail, S.
ABSTRACT: Recently, there is greater concern for industries to maintain lubricant flow along the extrusion process, which is important to obtain the best quality of the final products. One of the most cost-effective methods is surface texturing. In this research, surface texturing was embedded on a tapered die sliding contact surface to explore its effectiveness on a finished product from a cold extrusion process. Palm oil–based lubricant was tested for cold extrusion processes and mineral oil was used for comparison purposes. It was found that a textured tapered die (TA) performed a diminished extrusion load compared to an untextured tapered die (NA) and improved the performance of other test parameters. As an alternative lubricant, refined, bleached, and deodorized (RBD) palm kernel oil presents results similar to those of commercial extrusion oil in terms of extrusion load and product quality. Based on the results, it is proven that surface texturing and palm oil–based lubricant can be considered as an alternative approach for implementation in industry.